PENERAPAN METODE DEMPSTER SHAFER UNTUK MENDIAGNOSIS PENYAKIT PADA TANAMAN KOL - Rizki Hannum; Machrani Adi Putri Siregar; Nenna Isya Syaputri (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
Cabbage is a seasonal plant that contains vitamin A, vitamin B complex, iron, potassium, rivoplafin and folic acid. The problems that often occur with cabbage are pests and diseases which are a serious problem, if not handled properly, the plants may die or not grow properly. Diseases that often attack cabbage are wilting leaves, root rot, fruit and flowers. The limited time of an agricultural expert is an obstacle for farmers to carry out consultations to solve a problem to get the best solution. The process of diagnosis with the help of experts can be applied to the Dempster Shafer method. The Dempster Shafer method is a solution in diagnosis because this method can provide additional information in the form of the percentage of confidence in the disease suffered by an object. The results of this study indicate that from the symptoms obtained using the Dempster Shafer method in 3 cases given by farmers, the percentage of confidence was 82% for wet rot disease, 73.3% for black leg rot disease and 73% for powdery mildew disease, so this method assessed can be applied to the diagnosis of diseases in cabbage plants